Craniopharyngioma: Recurrence Factors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Factors predictive of recurrence and functional outcome were determined in a retrospective clinicopathological analysis of 56 patients (26 children and 30 adults) operated on for craniopharyngioma since 1981 at New York University Medical Center.